Phase retrieval by constrained power inflation and signum flipping. Issue 12 (10th December 2016) - Laganà, A. R.; Morabito, A. F.; Isernia, T.
Abstract: In this paper we consider the problem of retrieving a signal from the modulus of its Fourier transform (or other suitable transformations) and some additional information, which is also known as "Phase Retrieval" problem. The problem arises in many areas of applied Sciences such as optics, electron microscopy, antennas, and crystallography. In particular, we introduce a new approach, based on power inflation and tunneling, allowing an increased robustness with respect to the possible occurrence of false solutions. Preliminary results are presented for the simple yet relevant case of one‐dimensional arrays and noisy data. Key Points: Accurate and reliable solution procedures for Phase Retrieval problems are of interest in very many cases All the available solution procedures are subject to the possible trapping into "false solutions" A new point of view and a new procedure allowing some increased robustness with respect to trapping are proposed and discussed